Residual effects of two consecutive applications of municipal solid waste compost and fertilizers on biomass production and yield of rice (Oryza sativa L.) - Jahan, Israt; Rahman, M. M.; Hasan, Muhammad Mahmudul; Hossain, Mohammad Emdad; Haque, Ahmad Numery Ashfaqul; Shamsuzzaman, S. M.; Rafii, M. Y. (Bangladesh Botanical Society, 2017)
A field experiment was conducted to evaluate the residual effects of municipal solid waste (MSW) compost and inorganic fertilizer on the yield, biomass production and nutrient uptake of rice. The treatments used in the experiment were: T0 (no fertilizer/compost), T1 (100% recommended doses of NPKS), T2 (compost 5.0 t/ha), T3 (compost 5 t/ha +100% RDF), T4 (compost 7.5 t/ha), T5 (compost 7.5 t/ha +100% RDF), T6 (compost 10 t/ha), T7 (compost 10 t/ha +100% RDF) and T8 (compost 20 t/ha). Residual effects of MSW (10 t/ha) with 100% RDF (T7) produced the highest grain (5.15 t/ha) and straw (7.21 t/ha) yield. The NPKS uptake by BINAdhan7 was markedly influenced by the residual effects of MSW compost and inorganic fertilizers. Municipal solid waste compost with 100% RDF was found to exert the best residual effect for obtaining the maximum yield of rice.